2016
DOI: 10.1155/2016/7521798
|View full text |Cite
|
Sign up to set email alerts
|

Massive Cerebrospinal Fluid Leak of the Temporal Bone

Abstract: Cerebrospinal fluid (CSF) leakage of the temporal bone region is defined as abnormal communications between the subarachnoidal space and the air-containing spaces of the temporal bone. CSF leak remains one of the most frequent complications after VS surgery. Radiotherapy is considered a predisposing factor for development of temporal bone CSF leak because it may impair dural repair mechanisms, thus causing inadequate dural sealing. The authors describe the case of a 47-year-old man with a massive effusion of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…1,3 CSF leaks, recognized intraoperatively or through imaging, can be managed conservatively or surgically. 4 Conservative management includes bed rest, an epidural blood patch, and/or fibrin glue. 1,5 Those patients for whom conservative management fails may require a neurosurgeon to either suture the tear closed, use a dural sealant such as fibrin glue, place a fat or muscle graft, insert a patch, or use a combination of techniques to achieve a watertight closure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 CSF leaks, recognized intraoperatively or through imaging, can be managed conservatively or surgically. 4 Conservative management includes bed rest, an epidural blood patch, and/or fibrin glue. 1,5 Those patients for whom conservative management fails may require a neurosurgeon to either suture the tear closed, use a dural sealant such as fibrin glue, place a fat or muscle graft, insert a patch, or use a combination of techniques to achieve a watertight closure.…”
mentioning
confidence: 99%
“… 7 However, in some cases, the edges of the native dura may be so friable that suturing or clipping to the dura results in incomplete seals, tears, or leaks through the suture holes. 4 , 8 Additionally, those with a history of radiotherapy to or near the spine may have compromised dural blood supply, extensive scarring or adhesions, and/or tissue hypoxia, thereby weakening the dura mater, increasing the likelihood of CSF leaks, and requiring a more intensive dural closure. 4 , 8 Thus, this study presents a novel approach to treating a radiation-induced dural injury and CSF leak as well as expansive dural tears by the use of a two-layer intradural and extradural patch graft.…”
mentioning
confidence: 99%
“…Firstly, unilateral tympanomastoid effusion is known to be associated with LTBCs, both clinically and on imaging studies. 15,22 GRE 3D T 2 W sequences such as CISS are optimal for the analysis of the differing fluid composition of tympanomastoid fluid due to the utilisation of heavier T2 weighting and increased signal-to-noise ratios. 23,24 Breen et al studied patients with temporal bone CSF leaks, although without cephaloceles in the majority of cases, and found that tympanomastoid signal isointense to CSF was 100% specific and 76% sensitive for the presence of a CSF leak.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents a detailed description of all the PCF SL patients. Table 1 does not include (a) nonspontaneous (iatrogenic, after surgery or radiotherapy, post-traumatic) PCF liquorrhea; 7,8 (b) spontaneous PCF pneumocephalus due to bone defects that did not manifest in the form of SL; [9][10][11] (c) PCF bone defects or encephalocele (herniation) not accompanied by SL (or if this fact was not mentioned in the report); 12,13 (d) clivus defects manifesting in the form of SL, which, in turn, also can be attributed to PCF defects, but we believe that such pathology requires individual analysis; 14,15 (e) literature reviews without specifying own experience of PCF SL treatment; 16 and (f) reports where a PCF defect was mentioned for the general group of SL patients, but that had no required observation data (age, sex, symptoms, defect location, approach, complications, and so forth) 3,17,18…”
Section: Methodsmentioning
confidence: 99%